In-silico analysis unveiling the role of cancer stem cells in immunotherapy resistance of immune checkpoint-high pancreatic adenocarcinoma - Udit Basak; Sumon Mukherjee; Sourio Chakraborty; Gaurisankar Sa; Shubhra Ghosh Dastidar; Tanya Das (Scientific Reports)
Abstract Although immune checkpoint (IC) inhibition is a major treatment modality in cancer-immunotherapy, multiple cancers show low response. Our in-silico exploration by mining cancer datasets using R2, available clinical trial data, and Kaplan–Meier analysis from GEPIA depicted that unlike low-responder (LR) cancers, high-responder (HR) cancers furnish higher IC expression, that upon lowering may provide better prognosis. Contrastingly, pancreatic adenocarcinoma (PAAD) demonstrated high IC expression but low immunotherapy-response. Infiltration scores from TIMER2.0 revealed higher pro-tumor immune subsets and cancer-associated fibroblasts (CAFs) while depicting lower anti-tumor immune subsets in PAAD as compared to HR lung adenocarcinoma (LUAD). Additionally, bioinformatic tool cBioportal showed lesser tumor mutational burden, mismatch repair deficiency and greater percent of driver mutations in TP53, KRAS and CDKN2A in PAAD, supporting its higher immunotherapy-resistance than LUAD. Our search for the ‘key’ immunotherapy response-deciding factor(s) revealed cancer stem cells (CSCs), the known contributors of therapy-resistance and immuno-evasion, to be positively correlated with above-mentioned driver mutations, pro-tumor immune and CAF subsets; and that PAAD furnished higher expression of CSC genes than LUAD. UMAP/tSNE analyses revealed that high CSC signature is positively correlated with immunotherapy-resistance genes and pro-cancer immune cells, while negatively with cytotoxic-T cells in PAAD. Our in-silico study explains the low immunotherapy-response in high IC-expressing PAAD, wherein CSC plays a pivotal role. Further exploration portrayed correlation of CSCs with immunotherapy-resistance in other LR and HR cancers too, substantiating the need for personalized CSC evaluation and targeting for successful immunotherapy outcomes.